The Talent Management Of Art Design In Universities In Digital Era Under Liaoning Province - Yueqi, Wang; Jirarotephinyo , Nitwadee; Chanphong, Somsak (Journal of Roi Kaensarn Academi, 2024)
The objective of this study were (1) to explore the components of the talent management in digital era of university art design majors; (2) to verify the talent management components in digital era of university art design majors; (3) to propose the talent management guideline in digital era of university art design majors in Liaoning Province. The study was a mixed study involving 2341 leaders, professional teachers and administrators from 10 public universities in Liaoning Province. Using the Krejcie and Morgan table, the researchers identified 331 individuals as the sample size by stratified random sampling technique. Targeted screening of 7 key information providers. The tools for data collection include the collection and analysis of relevant literature, semi-structured interviews with key insiders, questionnaire surveys and focus group discussions. Data analysis and statistics are mainly carried out through the statistical package analysis software used to verify the model analyze. The research results show that: (1) the talent management in digital era in Liaoning Province is divided into 4 components consistent of: university talent management, digital era, art design major and management policy. (2) the talent management components in digital era of university art design majors were consistent with the empirical data of research. (3) there are 45 guidelines for the talent management in digital era of university art design majors in Liaoning Province.